2014
DOI: 10.1016/j.matchemphys.2014.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Chloride adsorption by calcined layered double hydroxides in hardened Portland cement paste

Abstract: h i g h l i g h t sWe examine the adsorption equilibrium and kinetics of CLDH in the hydrated cement. CLDH capacity to bind chloride ions in the hydrated cement paste is determined. We model chloride adsorption by CLDH through the cement matrix. CLDH reforms the layered structure with ion adsorption in the cement matrix. s t r a c tThis study investigated the feasibility of using calcined layered double hydroxides (CLDHs) to prevent chloride-induced deterioration in reinforced concrete. CLDHs not only adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 50 publications
(41 reference statements)
0
41
0
Order By: Relevance
“…In the above-mentioned studies, the intercalated anions were nitrite (corrosion inhibitor), nitrate, carbonate, and chloride. The most commonly studied LDH is by far MgAl-LDH [20][21][22]24,27,32,35,[37][38][39][41][42][43][44][45][46][47]49,50], followed by CaAl [16][17][18]26,[32][33][34]40], hydrotalcite [23,29,36], and modified hydrotalcite [25,28,31]. ZnAl-LDH is a new composition that has been studied in only two papers [51,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above-mentioned studies, the intercalated anions were nitrite (corrosion inhibitor), nitrate, carbonate, and chloride. The most commonly studied LDH is by far MgAl-LDH [20][21][22]24,27,32,35,[37][38][39][41][42][43][44][45][46][47]49,50], followed by CaAl [16][17][18]26,[32][33][34]40], hydrotalcite [23,29,36], and modified hydrotalcite [25,28,31]. ZnAl-LDH is a new composition that has been studied in only two papers [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…The use of LDH to control the cement hydration kinetics has been studied by several groups [18][19][20][21]. However, most of the work with LDH in concrete is dedicated to the mitigation of steel rebars corrosion, either in chloride media [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] or carbonated concrete [32,[41][42][43][44][45][46][47][48]. Many studies have been done in simulated concrete pore solution [35,38,43,46], just a few in mortar [31,43] and only one in concrete [16].…”
mentioning
confidence: 99%
“…Another method that is commonly followed is the calcination [82,83] method where LDH is heated to high temperatures in order to remove interlayer water/OH − and interlayer anions, thereby losing it layered structures and forming amorphous metallic oxides. Upon rehydration the LDH is able to reconstruct its structure using its "memory effect" property [84] upon exposure to water and also intercalate new anions which were not present in the parent LDH [80].…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Also, it is worthwhile to note from the literature that, when CLDH was blended with calcium sulfoaluminate cement, changes in sample strength were insignificant [35]; when it was blended into Portland cement, decreases in sample strength were observed [36,37]. In those cementitious systems the hydrotalcite-like phase is not an intrinsic reaction product; therefore the recrystallised CLDH in those systems performs most likely just as a filler, even though it may also consume water as it rehydrates, and reduce the overall water/binder ratio in those systems.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…CLDH is produced by thermal treatment of a layered double hydroxide mineral such as hydrotalcite, which contains a positively charged layer structure that allows exchange of interlayer anions [32][33][34]. Recently, CLDH has begun to be used as a 'smart' chemical addition for cementitious materials due to its ion-exchange properties, enhancing performance and durability [14,[35][36][37][38]. A recent study also demonstrated the high chloride binding capacity of the different layered double hydroxide (LDH) type phases typically identified in alkaliactivated slag paste [39].…”
Section: Introductionmentioning
confidence: 99%